Complejidad en proyectos: generación de un modelo en el sector de la construcción colombiano - Sarmiento-Rojas, Jorge-Andrés; Hernández-Carrillo, Carlos-Gabriel; Güiza-Pinzón, Fabián-David (Revista Científica, 2023)
Complexity in project management is a scarcely understood topic in the construction sector, which is only associated with difficulty. However, this extends beyond this definition. Despite the fact that current project complexity models in Colombia are adequate, this economic activity has special characteristics that make it particular and little explored. This highlights the need for formulating a complexity model adapted to the Colombian context. To this effect, it was necessary to understand and characterize the sector, along with the proposal of a reference framework that addresses complexity in Colombian construction projects based on their business characteristics. This, aiming to understand the complexity of the construction sector and offer opportunities to improve project management and success, as well as business permanence.